2018
DOI: 10.1002/cpt.1064
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Pharmacodynamics of Buprenorphine in Neonatal Abstinence Syndrome

Abstract: Neonatal abstinence syndrome (NAS) is a condition affecting newborns that are exposed to an opioid in utero. In a randomized, controlled trial assessing the efficacy of buprenorphine and morphine in NAS, blood samples were analyzed from a subset of patients receiving buprenorphine along with NAS scores. The data were used to validate and adapt an existing model of buprenorphine in neonates and to identify relationships between buprenorphine or norbuprenorphine pharmacokinetics (PK) and efficacy or safety. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
3
32
0
1
Order By: Relevance
“…Data from the phase III BBORN trial based on this structural model revealed similar results to that seen in the phase I trial. 56 Kamatkar et al . described the PK of buprenorphine in 63 samples from a cohort of 20 NAS infants treated at the University of Cincinnati in an open-label approach.…”
Section: Buprenorphine Pk/pd In Nasmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the phase III BBORN trial based on this structural model revealed similar results to that seen in the phase I trial. 56 Kamatkar et al . described the PK of buprenorphine in 63 samples from a cohort of 20 NAS infants treated at the University of Cincinnati in an open-label approach.…”
Section: Buprenorphine Pk/pd In Nasmentioning
confidence: 99%
“…This is supported by observations of 1) increased clearance associated with worse NAS symptoms, 2) more severe NAS generally requiring a higher AUC to control symptoms, and 3) that higher average concentrations of buprenorphine were correlated with faster time to stabilization. 56 Major covariates that drive this variability in drug exposure and clearance have not been identified. However, the linkage between exposure and response when combined with disease state models will allow future simulations to identify regimens more likely to control symptoms quickly and minimize duration of pharmacologic treatment.…”
Section: Buprenorphine Pk/pd In Nasmentioning
confidence: 99%
“…The study used an indirect response model to assess the concentration‐response relationship between buprenorphine concentrations and Finnegan scores. Similarly, Moore et al 110 assessed the PK/PD relationship of neonates treated with buprenorphine for NOWS. The study predicted the PK of buprenorphine and its metabolite norbuprenorphine and used the MOTHER NAS Scale (a modified version of the Finnegan scoring system) to assess the PD of each neonate.…”
Section: Pharmacodynamics Of Opioids In Infants With Nowsmentioning
confidence: 99%
“…Because a growing number of pregnant opioid users receive buprenorphine maintenance therapy, concerns regarding the adverse effects of this long-lasting opioid on the brain function of offspring have received increasing attention [1][2][3][4]. Indeed, visuomotor dysfunction has been reported in children prenatally exposed to opioids [5].…”
Section: Introductionmentioning
confidence: 99%